The Effect of Divorce on Parents on The Ethics of Class 3 XIIA Students at State Vocational High School 2 Ponorogo - Noor Syahid; Irfan Wahyu Syifa (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
This study aims to determine the impact of divorce perents on Akhlak of students in SMKN 2 Ponorogo. The problems at SMKN 2 Ponorogo based on theresults of the preliminary research showed that the students whose parents divorcedat Ponorogo State Vocational High School was very much, of the total 1,075 students,about 90 students whose parents were divorced and about 130 students who werebroken home or his parents separated but not yet officially divorced. Based on thesubject matter studied, the impact of divorce on the Akhlak students in SMKN 2Ponorogo, the researchers used qualitative research, because the qualitativedescriptive method was the problem solving procedure investigated by describing thestate of the subject of research based on facts in the field. Data collection includessemi-structured interviews, observation and documentation. As for analyzing thedata, researchers used 3 techniques, namely data reduction, data display, andconclusion drawing. The results of this study reveal that there are 2 kinds effects ofparental divorce on students' morals or behaviors in school, the first is the positiveinfluence that students vent the divorce problem of both parents to study harder sothat they get good grades and become one of the outstanding students and the secondnegative influences are students becoming more reserved, lonely and arrogant. Thesolution for the child who is divorced is to maintain communication with both parents,show achievements to their parents, and maintain the full attention of both parents.This research also reveals that one of the causes divorce is economic problems andinfidelity.